RETRACTED: Targeted delivery of 5-fluorouracil, miR-532-3p, and si-KRAS to the colorectal tumor using layer-by-layer liposomes - Shahidi, Maryamsadat; Abazari, Omid; Dayati, Parisa; Haghiralsadat, Bibi Fatemeh; Oroojalian, Fatemeh; Tofighi, Davood (Frontiers in Bioengineering and Biotechnology, 2022)
Co-delivery of siRNA or miRNA with chemotherapeutic drugs into tumor sites is an attractive synergetic strategy for treating colorectal cancer (CRC) due to their complementary mechanisms. In the current work, a liposome nanoparticle (NP) coated by cationic chitosan (CS) using a controlled layer-by-layer (LbL) process was designed to deliver simultaneous si-KRAS, miRNA-532-3p, and 5-Fluorouracil (5-FU) into CRC cells. The LbL NPs exhibited a spherical structure with an average size of 165.9 nm and effectively protected si-KRAS and miRNA-532-3p against degradation by serum and nucleases. Interestingly, the LbL NPs were successfully entered into cells and efficiently promoted cytotoxicity and suppressed cancer cell migration and invasion. In vivo, the LbL NPs reduced tumor growth in SW480-tumor-bearing mice models. In conclusion, these results suggested that the LbL NPs co-loaded with 5-FU and miR-532-3p/si-KRAS might provide a promising potential strategy for inhibiting the malignant phenotypes of CRC cells.